Implementation of party projects as a way to strengthen the image of a public organization - Evstratova, Tatiana; Medvedeva, Natalia; Vetrova, Ekaterina; Kulikova, Olga; Kolosova, Olga (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
The purpose of the article was to identify the attitude of the population toward the Moscow Regional regional branch of the United Russia Party to improve the image of this public organization. Special sociological methods were used, including qualitative analysis of documents, secondary analysis of research results, survey methods. Based on the results of the survey, it was revealed that the implementation of party projects is a significant tool for forming the image of political organizations. An attractive image of an organization is the most important condition for its political success, which helps to bring the electorate to its side.